Screening Methods for Southern Chinch Bug Resistance in St. Augustinegrass - Huangjun Lu; Ronald Cherry (EDIS, 2014)
Relying on insecticides for southern chinch bug control raises turfgrass maintenance costs, increases the risk that insects will develop resistance to insecticides, and may damage the environment. Host-plant resistance is a relatively sustainable and environmentally sound option for management of this damaging insect pest.To develop new resistant varieties, plant materials must be screened for new sources of southern chinch bug resistance. Screening methods to measure host plant resistance of St. Augustinegrass to southern chinch bugs have measured nymphal and/or adult survival in so-called no-choice tests in which only the experimental plant materials were provided. There are four types of screening methods described in this 4-page fact sheet was written by Huangjun Lu and Ronald Cherry, and published by the UF Department of Entomology and Nematology, October 2014. (Photo credit: Long Ma, UF/IFAS Extension)